Thermal conductivity member and electronic device
By using anisotropic fillers such as �boron nitride or graphite resin films in thermal conductivity, the filling rate and directionality are adjusted, and the balance between thermal conductivity and electrical insulation and mechanical properties of existing thermal conductivity members is solved, achieving efficient thermal conductivity and good performance integration.
Patent Information
- Application Number
- JP2023169753
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
While the existing thermal conductivity members improve thermal conductivity, it is difficult to maintain good electrical insulation and mechanical properties, and the thermal fiber directionality is insufficient, affecting the thermal conductivity.
A resin film containing an anisotropic filler of �boron nitride or graphite is used to improve the thermal conductivity of the thermal conductivity members by adjusting the filling rate and directionality of the anisotropic filler in the resin film.
It significantly improves the thermal conductivity of the thermal conductivity members, while maintaining good electrical insulation and mechanical properties, enhancing the directionality of the thermal fibers, and improving the thermal conductivity.
Smart Images

Figure 2025059588000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive member and an electronic device. [Background technology]
[0002] As the processing power of electronic devices improves, the amount of heat generated by the electronic devices tends to increase. Therefore, heat dissipation measures that effectively dissipate heat to the outside of the device are becoming important. Thermally conductive members made of heat dissipating materials such as metals, ceramics, and resin compositions are used as such heat dissipation measures. Among these thermally conductive members, thermally conductive members formed from resin compositions are widely used because of their excellent electrical insulation properties, mechanical properties, heat resistance, chemical resistance, adhesiveness, and the like.
[0003] Also, in order to improve the thermal conductivity of the thermally conductive member, attempts have been made to efficiently conduct heat by arranging thermally conductive fibers in the direction of heat conduction.
[0004] Patent Document 1 discloses an insulating and thermally conductive sheet that contains insulating and highly thermally conductive fibers and a binder resin penetrating in the thickness direction, and is characterized in that at least one surface of the sheet has a surface roughness of 15 μm or less and the penetration density of the insulating and highly thermally conductive fibers penetrating in the thickness direction is 6% or more. Patent Document 1 also describes that it aims to provide a thermally conductive sheet with excellent insulation and thermal conductivity. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2013 / 100123 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a thermally conductive member having improved thermal conductivity. [Means for solving the problem]
[0007] According to the present invention, there are provided the following thermally conductive member and electronic device.
[0008] 1. A thermally conductive member comprising a resin film made of a cured product of a resin composition containing an anisotropic filler, The anisotropic filler has a scale-like shape, The thickness of the resin film T c The median diameter D of the anisotropic filler 50 Ratio of (D 50 / T c ) is between 1.1 and 5.0, The anisotropic filler comprises one or more selected from the group consisting of boron nitride and graphite; The thermally conductive member satisfies the following formula (1): C F ×I 100 / I 002 ≧2.4 (1) (In the above formula (1), I 002 is the diffraction peak intensity of the 002 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and I 100 is the diffraction peak intensity of the 100 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and C F is the filling rate of the anisotropic filler, and is expressed by the following formula (2): C F =V F / (V F +V R ) (2) In the formula (2), V F is the volume of the anisotropic filler in the resin film, and V R is the volume of the resin component in the resin film) [X-ray diffraction method] Using CuKα radiation as a radiation source, X-rays are irradiated in the thickness direction of the thermally conductive member under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, to perform X-ray diffraction. 2. The thermally conductive member described in 1., wherein the anisotropic filler comprises boron nitride. 3. The thermally conductive member according to 1 or 2, which satisfies the following formula (3): C F ×I 100 / I 002 <=20.0 (3) (In the above formula (3), C F , I 100 and I 002 is the same as that in formula (1) above. 4. A thermally conductive member comprising a resin film made of a cured product of a resin composition containing an anisotropic filler, The anisotropic filler has a scale-like shape, The thickness of the resin film T c The median diameter D of the anisotropic filler 50 Ratio of (D 50 / T c ) is between 1.1 and 5.0, the anisotropic filler comprises aluminum nitride; The thermally conductive member satisfies the following formula (4): C F ×I 100 / I 002 ≧1.0 (4) (In the above formula (4), I 002 is the diffraction peak intensity of the 002 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and I 100 is the diffraction peak intensity of the 100 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and C F is the filling rate of the anisotropic filler, and is expressed by the following formula (5): C F =V F / (V F +V R ) (5) In the formula (5), V F is the volume of the anisotropic filler in the resin film, and V R is the volume of the resin component in the resin film) [X-ray diffraction method] Using CuKα radiation as a radiation source, X-rays are irradiated in the thickness direction of the thermally conductive member under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, to perform X-ray diffraction. 5. The thermally conductive member according to 4., which satisfies the following formula (6): C F ×I 100 / I 002 <= 10.0 (6) (In the above formula (6), C F , I 100 and I 002 is defined as in formula (4) above. 6. A thermally conductive member comprising a resin film made of a cured product of a resin composition containing an anisotropic filler, The anisotropic filler has a scale-like shape, The thickness of the resin film T c The median diameter D of the anisotropic filler 50 Ratio of (D 50 / T c ) is between 1.1 and 5.0, the anisotropic filler comprises alumina; The thermally conductive member satisfies the following formula (7): C F ×I 113 / I 006 ≧5.0 (7) (In the above formula (7), I 006 is the diffraction peak intensity of the 006 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and I 113 is the diffraction peak intensity of the 113 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and C F is the filling rate of the anisotropic filler, and is expressed by the following formula (8): C F =V F / (V F +V R ) (8) (In the above formula (8), V F is the volume of the anisotropic filler in the resin film, and V Ris the volume of the resin component in the resin film) [X-ray diffraction method] X-ray diffraction is performed by irradiating the thermally conductive member with X-rays in the thickness direction under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, using CuKα radiation as the radiation source. 7. The thermally conductive member according to 6., which satisfies the following formula (9): C F ×I 113 / I 006 <= 50.0 (9) (In the above formula (9), C F , I 006 and I 113 is defined as in formula (7) above. 8. Volumetric median diameter D of the anisotropic filler 50 The thermally conductive member according to any one of 1. to 7., wherein the thickness is 20 μm or more and 100 μm or less. 9. Said C F 9. The thermally conductive member according to any one of 1. to 8., wherein the content is 10 vol % or more and 90 vol % or less. 10. The thermally conductive member according to any one of 1. to 9., wherein the resin composition contains a coupling agent. 11. The thermally conductive member according to any one of 1. to 10., wherein the resin composition includes a photosensitive resin composition. 12. The thermally conductive member according to any one of 1. to 11., wherein the resin composition includes a thermosetting resin composition. 13. The thermally conductive member according to any one of 1. to 12., wherein the resin composition contains a (meth)acrylic resin. 14. The thermally conductive member according to any one of 1. to 13., wherein the resin composition contains an epoxy resin. 15. The thermally conductive member according to any one of 1. to 14., wherein the resin composition contains a solvent. 16. The thermally conductive member according to any one of 1. to 15., wherein the resin composition contains a heat curing initiator. 17. The thermally conductive member according to any one of 1. to 16., wherein the resin composition contains a photocuring initiator. 18. The thermally conductive member according to any one of 1. to 17., further comprising a substrate. 19. The thermally conductive member according to claim 18, wherein the substrate comprises a metal foil. 20. The thermally conductive member according to claim 19, wherein the metal foil comprises copper foil. 21. The thermally conductive member according to any one of 1. to 20., wherein the thermally conductive member is in a B-stage state. 22. The thermally conductive member according to any one of 1. to 20., wherein the thermally conductive member is in a C-stage state. 23. A thermally conductive member according to any one of 1. to 22., an electronic component provided on the thermally conductive member; An electronic device comprising: Effect of the Invention
[0009] According to the present invention, it is possible to provide a thermally conductive member having improved thermal conductivity. [Brief description of the drawings]
[0010] [Figure 1] 1A to 1C are cross-sectional views that diagrammatically show an example of a method for producing a thermally conductive member according to an embodiment of the present invention. [Diagram 2] 1 is a cross-sectional view illustrating an example of an electronic device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the present invention will be described based on an embodiment.
[0012] In the present embodiment, when a numerical range is described stepwise, the upper and lower limits of each numerical range can be combined in any manner.
[0013] In this embodiment, the resin component in the resin film refers to the components in the resin film other than the filler.
[0014] The thermally conductive member of the present embodiment includes a resin film as an essential component and a substrate as an optional component, that is, the thermally conductive member of the present embodiment includes a thermally conductive member made of a resin film, and also includes a thermally conductive member having a resin film on a substrate such as a metal foil.
[0015] [Thermal conductive material] The thermally conductive member of this embodiment will be described below.
[0016] The thermally conductive member of the first embodiment includes a resin film made of a cured product of a resin composition containing an anisotropic filler. The anisotropic filler of the present embodiment has a scale-like shape. The thickness T c The median diameter D of the anisotropic filler of this embodiment 50 Ratio of (D 50 / T c ) is 1.1 or more and 5.0 or less, the anisotropic filler of the present embodiment contains one or more types selected from the group consisting of boron nitride and graphite, and the thermal conductive member of the present embodiment satisfies the following formula (1). C F ×I 100 / I 002 ≧2.4 (1) (In formula (1), I 002 is the diffraction peak intensity of the 002 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and I 100 is the diffraction peak intensity of the 100 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and C F is the filling rate of the anisotropic filler of this embodiment, and is represented by the following formula (2): C F =V F / (V F +V R ) (2) In formula (2), V F is the volume of the anisotropic filler of this embodiment in the resin film of this embodiment, and V R is the volume of the resin component in the resin film of this embodiment) [X-ray diffraction method] X-ray diffraction is performed by irradiating the thermal conductive member of this embodiment with X-rays in the thickness direction under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, using CuKα radiation as a radiation source.
[0017] Here, the volume-based median diameter D of the anisotropic filler 50 is the median diameter (D) of particles measured by a laser diffraction particle size distribution analyzer on a volume basis. 50 ).
[0018] Volume of anisotropic filler in resin film V F can be calculated from the content of the anisotropic filler and the specific gravity of the anisotropic filler. In addition, when the resin film does not contain any filler other than the anisotropic filler, the volume of the anisotropic filler in the resin film, V F The volume obtained by subtracting R In addition, when the resin film contains a filler other than the anisotropic filler, the volume of the anisotropic filler in the resin film V F The volume obtained by subtracting the volume of the fillers other than the anisotropic filler is the volume V of the resin component in the resin film. R It can be said that:
[0019] In formula (1), I 002 is the diffraction peak intensity of the 002 plane (2θ is approximately 27°) perpendicular to the plane direction of the anisotropic filler, and I 100 is the diffraction peak intensity of the 100 plane (2θ is approximately 42°) parallel to the plane direction of the anisotropic filler. 100 / I 002 A value of at least a certain level means that the planar direction of the anisotropic filler is parallel to the thickness direction of the thermal conductive member as shown in Figure 1 (3), that is, the degree of orientation of the anisotropic filler is at least a certain level. Also, C F is the filling rate of the anisotropic filler. Therefore, formula (1) shows that the filling rate of the anisotropic filler is equal to or higher than a certain level, and the degree of orientation of the anisotropic filler is equal to or higher than a certain level.
[0020] In the thermally conductive member of the first embodiment, D 50 / T c The value of is preferably 1.2 or more, more preferably 1.3 or more, even more preferably 1.4 or more, even more preferably 1.5 or more, and is preferably 4.0 or less, more preferably 3.5 or less, even more preferably 3.0 or less, even more preferably 2.8 or less, even more preferably 2.6 or less, even more preferably 2.4 or less, even more preferably 2.3 or less. 50 / T c When the value of is within the above range, the thermal conductivity of the thermally conductive member can be further improved.
[0021] In the thermally conductive member of the first embodiment, C F ×I 100 / I 002 From the viewpoint of further improving thermal conductivity, the value of is preferably 3.0 or more, more preferably 5.0 or more, even more preferably 7.0 or more, even more preferably 7.5 or more, even more preferably 8.0 or more, even more preferably 9.0 or more, even more preferably 10.0 or more, and even more preferably 11.0 or more.
[0022] In the thermally conductive member of the first embodiment, C F From the viewpoint of further improving thermal conductivity, the value is preferably 10 vol% or more, more preferably 30 vol% or more, even more preferably 50 vol% or more, even more preferably 55 vol% or more, even more preferably 60 vol% or more, and even more preferably 65 vol% or more, and from the viewpoint of the balance between thermal conductivity and production efficiency, the value is preferably 90 vol% or less, more preferably 85 vol% or less, even more preferably 80 vol% or less, and even more preferably 75 vol% or less.
[0023] The anisotropic filler of the present embodiment preferably contains boron nitride from the viewpoint of further improving the thermal conductivity of the thermally conductive member.
[0024] From the viewpoint of improving the balance of performance between thermal conductivity and production efficiency, the thermal conductive member of the first embodiment preferably satisfies the following formula (3). C F ×I 100 / I 002 <=20.0 (3) In formula (3), C F , I 100 and I 002 The definition of is the same as that in equation (1).
[0025] In the thermally conductive member of the first embodiment, C F ×I 100 / I 002 From the viewpoint of improving the performance balance between thermal conductivity and production efficiency, the value of is preferably 18.0 or less, more preferably 16.0 or less, even more preferably 15.0 or less, even more preferably 14.5 or less, even more preferably 14.0 or less, even more preferably 13.5 or less, and even more preferably 13.0 or less.
[0026] The thermally conductive member of the second embodiment includes a resin film made of a cured product of a resin composition containing an anisotropic filler. The anisotropic filler of the present embodiment has a scale-like shape. The thickness T c The median diameter D of the anisotropic filler of this embodiment 50 Ratio of (D 50 / T c ) is 1.1 or more and 5.0 or less, the anisotropic filler of this embodiment contains aluminum nitride, and the thermally conductive member of this embodiment satisfies the following formula (4). C F ×I 100 / I 002 ≧1.0 (4) (In formula (4), I 002 is the diffraction peak intensity of the 002 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and I 100 is the diffraction peak intensity of the 100 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and C F is the filling rate of the anisotropic filler of this embodiment, and is expressed by the following formula (5): C F =V F / (V F +V R ) (5) In equation (5), V F is the volume of the anisotropic filler of this embodiment in the resin film of this embodiment, and V R is the volume of the resin component in the resin film of this embodiment) [X-ray diffraction method] X-ray diffraction is performed by irradiating the thermal conductive member of this embodiment with X-rays in the thickness direction under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, using CuKα radiation as a radiation source.
[0027] Here, the volume-based median diameter D of the anisotropic filler 50 is the median diameter (D) of particles measured by a laser diffraction particle size distribution analyzer on a volume basis. 50 ).
[0028] Volume of anisotropic filler in resin film V F and the volume V of the resin component in the resin film R The calculation method is as described above.
[0029] In formula (4), I 002 is the diffraction peak intensity of the 002 plane (2θ is approximately 36.5°) perpendicular to the plane direction of the anisotropic filler, and I 100 is the diffraction peak intensity of the 100 plane (2θ is approximately 33.2°) parallel to the plane direction of the anisotropic filler. 100 / I 002 A value of at least a certain level means that the planar direction of the anisotropic filler is parallel to the thickness direction of the thermal conductive member as shown in Figure 1 (3), that is, the degree of orientation of the anisotropic filler is at least a certain level. Also, C F is the filling rate of the anisotropic filler. Therefore, formula (4) is an equation showing that the filling rate of the anisotropic filler is equal to or higher than a certain level, and the degree of orientation of the anisotropic filler is equal to or higher than a certain level.
[0030] In the thermally conductive member of the second embodiment, D 50 / T c The value of is preferably 1.2 or more, more preferably 1.3 or more, even more preferably 1.4 or more, even more preferably 1.5 or more, and is preferably 4.0 or less, more preferably 3.5 or less, even more preferably 3.0 or less, even more preferably 2.8 or less, even more preferably 2.6 or less, even more preferably 2.4 or less, even more preferably 2.3 or less. 50 / T c When the value of is within the above range, the thermal conductivity of the thermally conductive member can be further improved.
[0031] In the thermally conductive member of the second embodiment, C F ×I 100 / I 002 From the viewpoint of further improving the thermal conductivity, the value of is preferably 1.5 or more, more preferably 2.0 or more, even more preferably 2.5 or more, even more preferably 3.0 or more, and even more preferably 3.4 or more.
[0032] In the thermally conductive member of the second embodiment, C F From the viewpoint of further improving thermal conductivity, the value is preferably 10 vol% or more, more preferably 30 vol% or more, even more preferably 50 vol% or more, even more preferably 55 vol% or more, even more preferably 60 vol% or more, and even more preferably 65 vol% or more, and from the viewpoint of improving the performance balance between thermal conductivity and production efficiency, the value is preferably 90 vol% or less, more preferably 85 vol% or less, even more preferably 80 vol% or less, and even more preferably 75 vol% or less.
[0033] From the viewpoint of improving the balance between thermal conductivity and production efficiency, the thermal conductive member of the second embodiment preferably satisfies the following formula (6). C F ×I 100 / I 002 <= 10.0 (6) In formula (6), C F , I 100 and I002 The definition of is the same as that in equation (4).
[0034] In the thermally conductive member of the second embodiment, C F ×I 100 / I 002 From the viewpoint of improving the performance balance between thermal conductivity and production efficiency, the value of is preferably 9.0 or less, more preferably 8.0 or less, even more preferably 7.0 or less, still more preferably 6.5 or less, and even more preferably 6.0 or less.
[0035] The thermally conductive member of the third embodiment includes a resin film made of a cured product of a resin composition containing an anisotropic filler. The anisotropic filler of the present embodiment has a scale-like shape. The thickness T c The median diameter D of the anisotropic filler of this embodiment 50 Ratio of (D 50 / T c ) is 1.1 or more and 5.0 or less, the anisotropic filler of this embodiment contains alumina, and the thermally conductive member of this embodiment satisfies the following formula (7). C F ×I 113 / I 006 ≧5.0 (7) (In formula (7), I 006 is the diffraction peak intensity of the 006 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and I 113 is the diffraction peak intensity of the 113 plane of the X-ray diffraction chart obtained by the [X-ray diffraction method] below, and C F is the filling rate of the anisotropic filler of this embodiment, and is expressed by the following formula (8): C F =V F / (V F +V R ) (8) In equation (8), V F is the volume of the anisotropic filler of this embodiment in the resin film of this embodiment, and V R is the volume of the resin component in the resin film of this embodiment) [X-ray diffraction method] X-ray diffraction is performed by irradiating the thermal conductive member of this embodiment with X-rays in the thickness direction under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, using CuKα radiation as a radiation source.
[0036] Here, the volume-based median diameter D of the anisotropic filler 50 is the median diameter (D) of particles measured by a laser diffraction particle size distribution analyzer on a volume basis. 50 ).
[0037] Volume of anisotropic filler in resin film V F and the volume V of the resin component in the resin film R The calculation method is as described above.
[0038] In equation (7), I 006 is the diffraction peak intensity of the 006 plane (2θ is approximately 41.6°) perpendicular to the plane direction of the anisotropic filler, and I 113 is the diffraction peak intensity of the 113 plane (2θ is approximately 43.3°) parallel to the plane direction of the anisotropic filler. 113 / I 006 A value of at least a certain level means that the planar direction of the anisotropic filler is parallel to the thickness direction of the thermal conductive member as shown in Figure 1 (3), that is, the degree of orientation of the anisotropic filler is at least a certain level. Also, C F is the filling rate of the anisotropic filler. Therefore, formula (7) shows that the filling rate of the anisotropic filler is equal to or greater than a certain level, and the degree of orientation of the anisotropic filler is equal to or greater than a certain level.
[0039] In the thermally conductive member of the third embodiment, D 50 / T cThe value of is preferably 1.2 or more, more preferably 1.3 or more, even more preferably 1.4 or more, even more preferably 1.5 or more, and is preferably 4.0 or less, more preferably 3.5 or less, even more preferably 3.0 or less, even more preferably 2.8 or less, even more preferably 2.6 or less, even more preferably 2.4 or less, even more preferably 2.3 or less. 50 / T c When the value of is within the above range, the thermal conductivity of the thermally conductive member can be further improved.
[0040] In the thermally conductive member of the third embodiment, C F ×I 113 / I 006 From the viewpoint of further improving the thermal conductivity, the value of is preferably 6.0 or more, more preferably 7.0 or more, and further preferably 10.0 or more.
[0041] In the thermally conductive member of the third embodiment, C F From the viewpoint of further improving thermal conductivity, the value is preferably 10 vol% or more, more preferably 30 vol% or more, even more preferably 50 vol% or more, even more preferably 55 vol% or more, even more preferably 60 vol% or more, and even more preferably 65 vol% or more, and from the viewpoint of the balance between thermal conductivity and production efficiency, the value is preferably 90 vol% or less, more preferably 85 vol% or less, even more preferably 80 vol% or less, and even more preferably 75 vol% or less.
[0042] In the thermally conductive member of the third embodiment, from the viewpoint of improving the balance of performance between thermal conductivity and production efficiency, the thermally conductive member preferably satisfies the following formula (9). C F ×I 113 / I 006 <= 50.0 (9) In formula (9), C F , I 006 and I 113 The definition of is the same as that in equation (7).
[0043] In the thermally conductive member of the third embodiment, C F×I 113 / I 006 From the viewpoint of improving the performance balance between thermal conductivity and production efficiency, the value of is preferably 48.0 or less, more preferably 45.0 or less, even more preferably 43.0 or less, even more preferably 41.0 or less, and even more preferably 40.0 or less.
[0044] The mechanism by which the thermal conductivity of the thermally conductive member of this embodiment is improved is not clear, but the following mechanism is presumed. First, it is believed that the thermal conductivity of the thermally conductive member of this embodiment is improved because the filling rate of the anisotropic filler is equal to or higher than a certain level and the degree of orientation of the anisotropic filler is equal to or higher than a certain level. In addition, the median diameter D 50 and the thickness of the resin film T c The closeness of the values of a and b allows a single piece of anisotropic filler to form a path in the thickness direction of the resin film, which is believed to further improve the thermal conductivity.
[0045] <One example of the manufacturing method of the thermally conductive member according to the present embodiment> The present inventors have investigated a method for producing the thermally conductive member of this embodiment and found that the anisotropic filler can be appropriately oriented by magnetic field orientation carried out under specific conditions. Here, an example of a method for appropriately orienting the anisotropic filler and producing the thermally conductive member according to this embodiment will be described with reference to Fig. 1. Note that the above conditions are merely an example, and the method for producing the thermally conductive member according to this embodiment is not limited to the method described below. First, a sheet having a resin film 2 made of a resin composition containing a resin and anisotropic filler 5 on a substrate 1 is prepared to obtain a laminate A (FIG. 1(1)). Next, the laminate A is placed on a magnet 3 (for example, a permanent magnet of about 0.2 to 0.4 T) and a magnetic field is applied. This causes the anisotropic filler 5 to be magnetically oriented (FIG. 1(2)). Next, the resin film 2 is cured to obtain the thermally conductive member 20 (FIG. 1(3)).
[0046] <Ingredients> Hereinafter, each component contained in the thermally conductive member of the present embodiment will be described.
[0047] The thermally conductive member of the present embodiment contains anisotropic filler. In this embodiment, the anisotropic filler refers to a filler that imparts anisotropy to a thermally conductive member by being blended with the thermally conductive member. Anisotropy generally refers to physical properties that differ depending on the direction, but in this embodiment, it refers to thermal conductivity that differs depending on the direction. In other words, blending the anisotropic filler in this embodiment makes it possible to obtain a thermally conductive member that has different thermal conductivity depending on the direction.
[0048] In the thermally conductive member of this embodiment, the anisotropic filler has a flaky shape. The scaly anisotropic filler may be monodisperse particles or agglomerated particles, but is preferably agglomerated particles from the viewpoint of further improving the thermal conductivity of the thermally conductive member. The agglomerated particles of the scaly anisotropic filler may be sintered particles or non-sintered particles.
[0049] The volume-based median diameter D of the anisotropic filler of this embodiment 50 From the viewpoint of further improving the thermal conductivity of the thermal conductive member, the thickness is preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 μm or more, and from the viewpoint of improving the balance of performance such as moldability, appearance, and flexibility, the thickness is preferably 100 μm or less, more preferably 80 μm or less, even more preferably 60 μm or less, and even more preferably 40 μm or less.
[0050] Here, the volume-based median diameter D of the anisotropic filler 50 is the median diameter (D) of particles measured by a laser diffraction particle size distribution analyzer on a volume basis. 50 ).
[0051] Filling rate C of the anisotropic filler in the thermal conductive member of this embodiment FFrom the viewpoint of further improving thermal conductivity, it is preferably 10 vol% or more, more preferably 30 vol% or more, even more preferably 50 vol% or more, even more preferably 55 vol% or more, even more preferably 60 vol% or more, and even more preferably 65 vol% or more, and from the viewpoint of improving the performance balance between thermal conductivity and production efficiency, it is preferably 90 vol% or less, more preferably 85 vol% or less, even more preferably 80 vol% or less, and even more preferably 75 vol% or less.
[0052] In the thermally conductive member of this embodiment, the surface of the anisotropic filler is preferably treated with a coupling agent, which improves the affinity between the anisotropic filler and the organic component and improves the dispersibility of the anisotropic filler.
[0053] In the thermally conductive member of the present embodiment, the resin composition of the present embodiment preferably contains a coupling agent, which improves the compatibility between the anisotropic filler and the organic component and improves the dispersibility of the anisotropic filler.
[0054] The type of coupling agent is not particularly limited, and known ones can be used, for example, silane coupling agent can be mentioned.Silane coupling agent can be mentioned, for example, vinyl group-containing silane coupling agent such as vinyltrimethoxysilane and vinyltriethoxysilane; epoxy group-containing silane coupling agent such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane and 3-glycidoxypropyltriethoxysilane; (meth)acrylic group-containing silane coupling agent such as 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane and 3-acryloxypropyltrimethoxysilane.
[0055] In the thermally conductive member of the present embodiment, for example, the resin composition of the present embodiment includes a photosensitive resin composition.
[0056] In the thermally conductive member of this embodiment, for example, the resin composition of this embodiment includes a thermosetting resin composition.
[0057] The resin composition of the present embodiment preferably contains a (meth)acrylic resin from the viewpoint of improving the balance of performance among moldability, appearance, and flexibility. In this specification, the term "(meth)acrylic" refers to a concept that includes both acrylic and methacrylic. The same applies to similar terms such as "(meth)acrylate" and "(meth)acryloyl".
[0058] The type of (meth)acrylic resin is not particularly limited, but for example, a resin obtained by polymerizing a monomer containing a (meth)acrylic acid ester as a main component (50 mass % or more, preferably 70 mass % or more, and more preferably 90 mass % or more) can be used. The (meth)acrylic acid ester is, for example, one or more selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-propyl (meth)acrylate, chloro-2-hydroxyethyl (meth)acrylate, diethylene glycol mono(meth)acrylate, methoxyethyl (meth)acrylate, glycidyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and isobornol (meth)acrylate.
[0059] When the resin composition of the present embodiment contains a (meth)acrylic resin, the content of the (meth)acrylic resin per 100 parts by mass of the resin composition of the present embodiment is, from the viewpoint of improving the performance balance of moldability, appearance, and flexibility, preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, and from the viewpoint of further improving thermal conductivity, preferably 90 parts by mass or less, more preferably 80 parts by mass or less, even more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, and even more preferably 50 parts by mass or less.
[0060] The resin composition of the present embodiment preferably contains an epoxy resin from the viewpoint of improving the balance of performance among moldability, appearance, and flexibility.
[0061] The type of epoxy resin is not particularly limited, and examples thereof include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, bisphenol S type epoxy resin, bisphenol M type epoxy resin (4,4'-(1,3-phenylenediisopridiene) bisphenol type epoxy resin), bisphenol P type epoxy resin (4,4'-(1,4-phenylenediisopridiene) bisphenol type epoxy resin), and bisphenol Z type epoxy resin (4,4'-cyclohexydiene bisphenol type epoxy resin); novolac type epoxy resins such as phenol novolac type epoxy resin, cresol novolac type epoxy resin, tetraphenol group ethane type novolac type epoxy resin, and novolac type epoxy resin having a condensed ring aromatic hydrocarbon structure; and Epoxy resins; aryl alkylene type epoxy resins such as xylylene type epoxy resins and epoxy resins having a biphenyl aralkyl skeleton; naphthylene ether type epoxy resins; naphthol type epoxy resins; naphthalene diol type epoxy resins; bifunctional to tetrafunctional epoxy type naphthalene resins such as 1,6-dihydroxynaphthalene type epoxy resins, 2,7-dihydroxynaphthalene type epoxy resins, 1,5-dihydroxynaphthalene type epoxy resins, 1,4-dihydroxynaphthalene type epoxy resins, and 2,6-dihydroxynaphthalene type epoxy resins; binaphthyl type epoxy resins; naphthalene type epoxy resins such as epoxy resins having a naphthalene aralkyl skeleton; anthracene type epoxy resins; epoxy resins having a dicyclopentadiene skeleton; norbornene type epoxy resins; epoxy resins having an adamantane skeleton; fluorene type epoxy resins;It includes one or more epoxy resins having a phenol aralkyl skeleton, and is preferably one or more epoxy resins selected from the group consisting of bisphenol A type epoxy resins, bisphenol F type epoxy resins, epoxy resins having a dicyclopentadiene skeleton, epoxy resins having a biphenyl skeleton, epoxy resins having an adamantane skeleton, naphthalene diol type epoxy resins, epoxy resins having a phenol aralkyl skeleton, epoxy resins having a biphenyl aralkyl skeleton, and epoxy resins having a naphthalene aralkyl skeleton;
[0062] When the resin composition of the present embodiment contains an epoxy resin, the content of the (meth)acrylic resin per 100 parts by mass of the resin composition of the present embodiment is, from the viewpoint of improving the performance balance of moldability, appearance, and flexibility, preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, and from the viewpoint of further improving thermal conductivity, preferably 90 parts by mass or less, more preferably 80 parts by mass or less, even more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, and even more preferably 50 parts by mass or less.
[0063] The resin composition of the present embodiment preferably contains a solvent. By containing a solvent in the resin composition, the viscosity of the resin composition can be reduced, and thus the anisotropic filler 5 can be more easily oriented.
[0064] The type of the solvent is not particularly limited, and examples thereof include alcohols such as ethyl alcohol, propyl alcohol, butyl alcohol, pentyl alcohol, hexyl alcohol, heptyl alcohol, octyl alcohol, nonyl alcohol, decyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl methoxybutanol, α-terpineol, β-terpineol, hexylene glycol, benzyl alcohol, 2-phenylethyl alcohol, isopalmityl alcohol, isostearyl alcohol, lauryl alcohol, ethylene glycol, propylene glycol, or glycerin; acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diacetone alcohol (4-hydroxy-4-methyl-2-pentanone), 2-octanone, isophorone ( Ketones such as 3,5,5-trimethyl-2-cyclohexen-1-one or diisobutyl ketone (2,6-dimethyl-4-heptanone); ethyl acetate, butyl acetate, diethyl phthalate, dibutyl phthalate, acetoxyethane, methyl butyrate, methyl hexanoate, methyl octanoate, methyl decanoate, methyl cellosolve acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, 1,2-diacetoxyethane, tributyl phosphate, tricresyl phosphate or tripentyl phosphate esters such as tetrahydrofuran, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, 1,2-bis(2-diethoxy)ethane or 1,2-bis(2-methoxyethoxy)ethane, ethylene glycol mono-2-ethylhexyl ether, tripropylene glycol mono-n-butyl ether, and the like; ester ethers such as 2-(2-butoxyethoxy)ethane acetate;The solvent may include one or more selected from the group consisting of ether alcohols such as 2-(2-methoxyethoxy)ethanol; hydrocarbons such as toluene, xylene, n-paraffin, isoparaffin, dodecylbenzene, turpentine oil, kerosene, and light oil; nitriles such as acetonitrile and propionitrile; amides such as acetamide and N,N-dimethylformamide; and silicone oils such as low molecular weight volatile silicone oils and volatile organic modified silicone oils, and more preferably tetrahydrofuran, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol The ethers include one or more selected from the group consisting of ethers such as ethyl diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, 1,2-bis(2-diethoxy)ethane or 1,2-bis(2-methoxyethoxy)ethane, ethylene glycol mono-2-ethylhexyl ether, and tripropylene glycol mono-n-butyl ether, and more preferably one or more selected from the group consisting of ethylene glycol mono-2-ethylhexyl ether and tripropylene glycol mono-n-butyl ether;
[0065] When the resin composition of this embodiment contains a solvent, the content of the solvent per 100 parts by mass of the resin composition of this embodiment is, from the viewpoint of improving moldability and making it easier to orient the anisotropic filler, preferably 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, and from the viewpoint of reducing the effort required to volatilize the solvent, preferably 80 parts by mass or less, more preferably 60 parts by mass or less, and more preferably 40 parts by mass or less.
[0066] The resin composition of the present embodiment contains, for example, a thermosetting initiator.
[0067] Examples of the thermal curing initiator include a thermal radical generator that generates radicals when heated, and a thermal cation generator that generates cations when heated. Examples of the thermal radical generator include azo compounds such as 2,2'-azobisbutyronitrile (AIBN) and peroxides such as benzoyl peroxide (BPO). Examples of thermal cation generators include iodonium salts and sulfonium salts. Commercially available products include the San-Aid series manufactured by Sanshin Chemical Industry Co., Ltd. and the Adeka Optomer series manufactured by ADEKA Corporation.
[0068] When the resin composition of the present embodiment contains a thermosetting initiator, the content of the thermosetting initiator is not particularly limited and can be set arbitrarily as necessary.
[0069] The resin composition of the present embodiment contains, for example, a photocuring initiator.
[0070] Examples of the photocuring initiator include a photoradical generator that generates radicals upon light irradiation, and a photocation generator that generates cations upon light irradiation. Examples of the photoradical generator include benzoin derivatives, benzil ketals, acetophenone, acylphosphine oxides, benzophenone, Michler's ketone, and thioxanthone. Commercially available products include the Irgacure series from IGM resins. Examples of photocation generators include iodonium salts and sulfonium salts. Commercially available products include the CPI series and IK series manufactured by San-Apro Co., Ltd.
[0071] When the resin composition of the present embodiment contains a photocuring initiator, the content of the photocuring initiator is not particularly limited and can be set arbitrarily as necessary.
[0072] The resin composition of the present embodiment may contain components other than those described above, for example, known components such as a polymerization inhibitor, an antifoaming agent, a surfactant, a colorant, etc. The content of these other components can be set arbitrarily as necessary.
[0073] The thermally conductive member of the present embodiment further includes, for example, a base material.
[0074] In the thermally conductive member of the present embodiment, from the viewpoint of further improving the thermal conductivity, the base material preferably includes a metal foil.
[0075] The type of metal foil is not particularly limited, but from the viewpoint of good processability, it preferably includes one or more types selected from the group consisting of copper foil, silver foil, gold foil, and aluminum foil, more preferably includes one or more types selected from the group consisting of copper foil and aluminum foil, and even more preferably includes copper foil.
[0076] The thermally conductive member of this embodiment may be in a B-stage state or a C-stage state.
[0077] [Electronic equipment] The electronic device of this embodiment will be described below.
[0078] The electronic device 50 of this embodiment includes a thermally conductive member 20 and an electronic component 30 on the thermally conductive member 20 .
[0079] The electronic device 50 of this embodiment may further include a heat sink 40. A heat sink is a component that absorbs heat generated by electronic components and dissipates the absorbed heat into the air to cool the electronic components. When the electronic device 50 of the present embodiment includes the heat sink 40, for example, the thermally conductive member 20 is sandwiched between the electronic component 30 and the heat sink 40. Since the thermally conductive member 20 has improved thermal conductivity, it can efficiently transfer heat generated in the electronic component 30 to the heat sink 40. When the thermally conductive member 20 is sandwiched between the electronic component 30 and the heat sink 40, the orientation of the thermally conductive member 20 is not particularly limited. However, from the viewpoint of cooling the electronic component more efficiently, it is preferable that the thermally conductive member 20 is sandwiched so that the base material 1 side faces the heat sink 40.
[0080] The type of electronic component 30 is not particularly limited. For example, a power semiconductor element may be used as the electronic component 30, and the electronic device may be a power module. Power semiconductor elements are made of wide band gap materials such as SiC, GaN, Ga2O3, or diamond, and are designed to be used at high voltages and currents, and therefore generate more heat than normal silicon chips (semiconductor elements), and therefore operate in high temperature environments. For example, power semiconductor elements are required to be used for long periods of time in high temperature operating environments, such as 200°C or higher or 250°C or higher. The thermally conductive member of the present embodiment has improved thermal conductivity, and can therefore be suitably used in power semiconductor elements. Examples of power semiconductor elements include rectifier diodes, power transistors, power MOSFETs, insulated gate bipolar transistors (IGBTs), thyristors, gate turn-off thyristors (GTOs), and triacs.
[0081] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. Furthermore, the present invention is not limited to the above-described embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES
[0082] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.
[0083] (Examples 1 to 3 and Comparative Example 1) First, a resin composition was applied onto a substrate (copper foil) to form a resin film. The thickness of the resin film after curing is T c The T of each Example and Comparative Example varies. c is shown in Table 1. The median diameter D of the flake boron nitride is 50The median diameter D of the flaky boron nitride in each of the examples and comparative examples was obtained by measuring the particle size distribution of the particles on a volume basis using a laser diffraction particle size distribution measuring device (manufactured by Horiba, Ltd., model name: HORIBA LA-950V2). 50 is shown in Table 1. The resin composition was prepared by mixing flake-shaped boron nitride (manufactured by Sanwa Material Co., Ltd.) surface-treated with 3-(methacryloyloxy)propyltrimethoxysilane in a (meth)acrylic photosensitive resin varnish with a filler loading rate of C after curing. F The values shown in Table 1 were obtained by mixing the components. The (meth)acrylic photosensitive resin varnish contains methacrylate, bisphenol F type epoxy resin, and acetophenone. The volume of the anisotropic filler in the resin film is V F was calculated from the content of the anisotropic filler and the specific gravity of the anisotropic filler. Also, the volume V of the resin component in the resin film R is the volume of the anisotropic filler in the resin film V F It was calculated by subtracting.
[0084] Next, the substrate on which the resin film was formed was placed on the south pole of a neodymium magnet with a magnetic force of 0.4 T with the substrate side facing the magnet, and dried at 60° C. for 30 minutes to magnetically align the scaly boron nitride 5.
[0085] Next, ultraviolet light with a wavelength of 256 nm was applied at an intensity of 6 mJ / cm 2 The resin film was cured by irradiating it with light at 180° C. for 200 seconds and then heating it at 180° C. for 60 minutes to obtain a thermally conductive member.
[0086] Comparative Example 2 A thermally conductive member was obtained in the same manner as in Example 1, except that the scaly boron nitride 5 was not subjected to magnetic field orientation.
[0087] X-ray diffraction was performed on the thermally conductive members of each of the examples and comparative examples by the following [X-ray diffraction method]. [X-ray diffraction method] X-ray diffraction was performed using a Rigaku X-ray diffraction device "Rigaku Ultima IV" with CuKα radiation as the radiation source, by irradiating X-rays in the thickness direction of the thermal conductive component under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, and a scanning speed of 2° / min. I of the thermal conductive members of each Example and Comparative Example 100 / I 002 and C F ×I 100 / I 002 The values are shown in Table 1.
[0088] The thermal conductivity of the thermally conductive members of each of the Examples and Comparative Examples was measured by the following [Thermal Conductivity Measurement Method]. The results are shown in Table 1. [Thermal conductivity measurement method] The thermal conductivity of the thermally conductive member in the thickness direction at 25° C. was measured using a thermal conductivity measuring device (manufactured by Netzsch, device name: LFA447 NanoFlash) by the laser flash method in accordance with JIS R 1611. The results are shown in Table 1.
[0089] [Table 1]
[0090] The thermal conductive member of the Example had a higher thermal conductivity than the thermal conductive member of the Comparative Example, which shows that the thermal conductive member of the Example has improved thermal conductivity. Moreover, from Example 2, it can be seen that even when the filling rate of the filler is low, the thermal conductivity tends to be high if the filler is oriented. [Explanation of symbols]
[0091] 1 Base material 2. Resin film 3. Magnets 5 Anisotropic filler (flake boron nitride) 20 Thermally conductive material 30 Electronic Components 40 Heat sink 50 Electronic equipment A Laminate A
Claims
1. A thermally conductive member including a resin film made of a cured product of a resin composition containing an anisotropic filler, The anisotropic filler has a scale-like shape, The thickness T of the resin film c The median diameter D of the anisotropic filler 50 The ratio (D 50 / T c ) is 1.1 or more and 5.0 or less, The anisotropic filler comprises one or more selected from the group consisting of boron nitride and graphite; The thermally conductive member satisfies the following formula (1): C F ×I 100 / I 002 ≧2.4 (1) (In the above formula (1), I 002 is the diffraction peak intensity of the 002 plane of the X-ray diffraction chart obtained by the following [X-ray diffraction method], and I 100 is the diffraction peak intensity of the 100 plane of the X-ray diffraction chart obtained by the following [X-ray diffraction method], and C F is the filling rate of the anisotropic filler, and is represented by the following formula (2): C F =V F / (V F +V R ) (2) In the formula (2), V F is the volume of the anisotropic filler in the resin film, and V R is the volume of the resin component in the resin film) [X-ray diffraction method] X-ray diffraction is performed by irradiating the thermally conductive member with X-rays in the thickness direction under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, using CuKα radiation as a radiation source.
2. The thermally conductive component of claim 1 , wherein the anisotropic filler comprises boron nitride.
3. The thermally conductive member according to claim 1 or 2, which satisfies the following formula (3): C F ×I 100 / I 002 ≦20.0 (3) (In the formula (3), C F , I 100 and I 002 is the same as that in formula (1) above.
4. A thermally conductive member including a resin film made of a cured product of a resin composition containing an anisotropic filler, The anisotropic filler has a scale-like shape, The thickness T of the resin film c The median diameter D of the anisotropic filler 50 The ratio (D 50 / T c ) is 1.1 or more and 5.0 or less, the anisotropic filler comprises aluminum nitride; The thermally conductive member satisfies the following formula (4): C F ×I 100 / I 002 ≧1.0 (4) (In the above formula (4), I 002 is the diffraction peak intensity of the 002 plane of the X-ray diffraction chart obtained by the following [X-ray diffraction method], and I 100 is the diffraction peak intensity of the 100 plane of the X-ray diffraction chart obtained by the following [X-ray diffraction method], and C F is the filling rate of the anisotropic filler, and is represented by the following formula (5): C F =V F / (V F +V R ) (5) In the formula (5), V F is the volume of the anisotropic filler in the resin film, and V R is the volume of the resin component in the resin film) [X-ray diffraction method] X-ray diffraction is performed by irradiating the thermally conductive member with X-rays in the thickness direction under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, using CuKα radiation as a radiation source.
5. The thermally conductive member according to claim 4 , which satisfies the following formula (6): C F ×I 100 / I 002 ≦10.0 (6) (In the formula (6), C F , I 100 and I 002 is the same as that in formula (4) above.
6. A thermally conductive member including a resin film made of a cured product of a resin composition containing an anisotropic filler, The anisotropic filler has a scale-like shape, The thickness T of the resin film c The median diameter D of the anisotropic filler 50 The ratio (D 50 / T c ) is 1.1 or more and 5.0 or less, the anisotropic filler comprises alumina; The thermally conductive member satisfies the following formula (7): C F ×I 113 / I 006 ≧5.0 (7) (In the above formula (7), I 006 is the diffraction peak intensity of the 006 plane of the X-ray diffraction chart obtained by the following [X-ray diffraction method], and I 113 is the diffraction peak intensity of the 113 plane of the X-ray diffraction chart obtained by the following [X-ray diffraction method], and C F is the filling rate of the anisotropic filler, and is expressed by the following formula (8): C F =V F / (V F +V R ) (8) (In the formula (8), V F is the volume of the anisotropic filler in the resin film, and V R is the volume of the resin component in the resin film) [X-ray diffraction method] X-ray diffraction is performed by irradiating the thermally conductive member with X-rays in the thickness direction under the conditions of a scanning axis of 2θ / θ, a sampling width of 0.02°, a scanning speed of 2° / min, an incident angle of 5°, and a reflection angle of 5°, using CuKα radiation as a radiation source.
7. The thermally conductive member according to claim 6 , which satisfies the following formula (9): C F ×I 113 / I 006 ≦50.0 (9) (In the formula (9), C F , I 006 and I 113 is the same as that in formula (7) above.
8. The volume-based median diameter D of the anisotropic filler 50 The thermal conductive member according to claim 1 , wherein the thickness is 20 μm or more and 100 μm or less.
9. Said C F The thermal conductive member according to claim 1 , wherein the content of the at least one component is 10% by volume or more and 90% by volume or less.
10. The thermally conductive member according to claim 1 , wherein the resin composition contains a coupling agent.
11. The thermally conductive member according to claim 1 , wherein the resin composition comprises a photosensitive resin composition.
12. The thermally conductive member according to claim 1 , wherein the resin composition comprises a thermosetting resin composition.
13. The thermally conductive member according to claim 1 , wherein the resin composition comprises a (meth)acrylic resin.
14. The thermally conductive member according to claim 1 , wherein the resin composition comprises an epoxy resin.
15. The thermally conductive member according to claim 1 , wherein the resin composition contains a solvent.
16. The thermally conductive member according to claim 1 , wherein the resin composition contains a heat curing initiator.
17. The thermally conductive member according to claim 1 , wherein the resin composition contains a photocuring initiator.
18. The thermally conductive member of claim 1 , 4 or 6 , further comprising a substrate.
19. 20. The thermally conductive member of claim 18, wherein the substrate comprises a metal foil.
20. 20. The thermally conductive member of claim 19, wherein the metal foil comprises a copper foil.
21. 7. The thermally conductive member of claim 1, 4 or 6, wherein the thermally conductive member is in a B-stage state.
22. 7. The thermally conductive member of claim 1, 4 or 6, wherein the thermally conductive member is in a C-stage state.
23. A thermally conductive member according to any one of claims 1, 4 and 6, an electronic component provided on the thermally conductive member; An electronic device comprising:
Citation Information
Patent Citations
Insulating and thermally conductive sheet
WO2013100123A1